Procedural pain management in Italy: learning from a nationwide survery involving centers of the Italian Association of Pediatric Hematology-Oncology - Po', Chiara (PAGEPress Publications, 2011)
Procedural pain is an important aspect of care in pediatrics, and particularly in pediatric oncology where children often consider this to be the most painful experience during their illness. Best recommended practice to control procedural pain includes both sedative-analgesic administration and non-pharmacological treatments, practiced in an adequate and pleasant setting by skilled staff. A nationwide survey has been conducted among the Italian Centers of Pediatric Hematology-Oncology to register operators' awareness on procedural pain, state of the art procedural pain management, operators' opinions about pain control in their center, and possible barriers impeding sedation-analgesia administration. Based on indications in the literature, we discuss the results of the survey to highlight critical issues and suggest future directions for improvement. Future objectives will be to overcome differences depending on size, improve operators' beliefs about the complexity of pain experience, and promote a global approach to procedural pain.